Antibiotic-Resistant Phenotype and Genotype of S. suis serotype 2 (SS2) Isolated from Humans in Bali, Indonesia - MAYURA, I PUTU BAYU -; TARINI, NI MADE ADI; Susilawathi, Ni Made; YULIANDARI, PUTU (Faculty of Medicine, Universitas Diponegoro, 2024)
Background: In recent times, meningitis, an infection primarily attributed to the zoonotic bacteria Streptococcus suis, has emerged as a significant public health concern in Bali, Indonesia. Their resistance to a multitude of antibiotics has emerged as a contemporary threat, as opposed to their virulence. There is a current lack of reported information regarding the genetic or phenotypic susceptibility pattern of S. suis to antibiotics in Bali.Objective: The objective of this research endeavor was to ascertain the antibiotic susceptibility pattern of S. suis isolates in Bali, either through phenotypic or genetic means.Methods: The Clinical Microbiology Laboratory of Prof. I.G.N.G. Ngoerah Hospital was consulted for the acquisition of clinical specimens. Since April 2016 until April 2022, the antibiotic sensitivity of isolates was identified and assessed using the VITEK 2 Compact (Biomeriuex®). Determining the serotype and antibiotic resistance genes genetically required PCR employing multiple primers.Results: Successful isolation of sixty-six S. suis isolates occurred primarily from cerebrospinal fluid. The results demonstrated that all isolates exhibited phenotypic resistance to tetracycline, with one isolate demonstrating co-resistance to tetracycline and erythromycin/clindamycin. It is additionally corroborated genetically through the amplification of the tetM gene in every isolate, including those that exhibited concurrent resistance to erythromycin and tetracycline. The intTn gene, which is a member of the conjugate transposon Tn916 family, was amplified and utilized for horizontal media gene transfer on S. suis plasmids carrying the resistance genes ermB and tetM.Conclusion: This research represents the initial investigation into the antibiotic resistance phenotype and genotype of S. suis serotype 2 (SS2) isolated from human subjects in Bali, Indonesia. The findings suggest that the pathogenicity and widespread dissemination of SS2 in the community may have been influenced by the extensive use of tetracycline and the horizontal acquisition of the genetic element Tn916 with tetM.